Comprehensive assessment of the prognosis of pancreatic cancer: peripheral blood neutrophil–lymphocyte ratio and immunohistochemical analyses of the tumour site. (3rd May 2016) - Takakura, Kazuki; Ito, Zensho; Suka, Machi; Kanai, Tomoya; Matsumoto, Yoshihiro; Odahara, Shunichi; Matsudaira, Hiroshi; Haruki, Koichiro; Fujiwara, Yuki; Saito, Ryota; Gocho, Takeshi; Nakashiro, Koh-Ichi; et al.
Abstract: Objective Several studies have suggested that an elevated neutrophil–lymphocyte ratio (NLR) is associated with a poorer prognosis in patients with pancreatic cancer (PC). The correlations between the NLR and immunohistochemical (IHC) analysis with regard to the prognosis of patients with PC remain to be elucidated. By using IHC findings, we determined the value of the NLR as a prognostic factor in patients with PC.Material and methods We collected the clinico-pathological data of 28 consecutive patients who underwent surgical resection for PC between January 2008 and December 2012 at The Jikei University Kashiwa Hospital. We investigated whether the NLR and IHC results were related and ensured the consistency of the prognosis of patients with PC.Results The Kaplan–Meier curves for the disease-free survival (DFS) and the overall survival (OS) revealed that an NLR ≥ 5 is an implicit factor for decreased DFS and OS in patients with PC ( p  =   0.003, p  < 0.001, log-rank test). The density of CD163 +  macrophages and CD66b +  neutrophils was significantly higher in the high NLR group; on the contrary, the density of CD20 +  lymphocytes was significantly higher in the low NLR group. Moreover, a Mann–Whitney U test showed that the NLR was significantly correlated with a high density of CD20 +  lymphocytes ( p  =   0.031) and CD163 +  macrophages ( p  =   0.023), while the NLR was not significantly correlated with CD66b +  neutrophils ( p  =   0.397).Conclusions Our results demonstrated the validity of the NLR by IHC analyses and we determined that a higher value of NLR is a trustworthy prognostic factor for patients with PC.